Effects of hypoxia on bronchial and alveolar epithelial cells linked to pathogenesis in chronic lung disorders - Berggren-Nylund, Rebecca; Ryde, Martin; Löfdahl, Anna; Ibáñez-Fonseca, Arturo; Kåredal, Monica; Westergren-Thorsson, Gunilla; Tufvesson, Ellen; Larsson-Callerfelt, Anna-Karin (Frontiers in Physiology, 2023)
Chronic lung disorders involve pathological alterations in the lung tissue with hypoxia as a consequence. Hypoxia may influence the release of inflammatory mediators and growth factors including vascular endothelial growth factor (VEGF) and prostaglandin E2. The aim of this work was to investigate how hypoxia in combination with profibrotic stimuli affects human lung epithelial cells and correlations to pathogenesis. Human bronchial (BEAS-2B) and alveolar (hAELVi) epithelial cells were exposed to either hypoxia (1% O2) or normoxia (21% O2) with or without transforming growth factor (TGF)-b1 during 24 h. mRNA expression of genes and proteins related to disease pathology was analysed with qPCR, ELISA or immunohistochemistry. Alterations in cell viability and metabolic activity were determined. In BEAS-2B and hAELVi, hypoxia significantly down-regulated genes related to fibrosis, mitochondrial stress, oxidative stress, apoptosis and inflammation whereas VEGFR2 was increased. Hypoxia increased the expression of Tenascin-C, whereas both hypoxia and TGF-b1 stimuli increased the release of VEGF, IL-6, IL-8 and MCP-1 in BEAS-2B. In hAELVi, hypoxia reduced the release of fibroblast growth factor, endothelial growth factor, PGE2, IL-6 and IL-8, whereas TGF-1 stimulus significantly increased the release of PGE2 and IL-6. TGF-b1 stimulated BEAS-2B cells showed a decreased release of VEGF-A and IL-8, while TGF-b1 stimulated hAELVi cells showed a decreased release of PGE2 and IL-8 during hypoxia compared to normoxia. Metabolic activity was significantly increased by hypoxia in both epithelial cell types. In conclusion, our data indicate that bronchial and alveolar epithelial cells respond differently to hypoxia and profibrotic stimuli. The bronchial epithelium appears more responsive to changes in oxygen levels and remodelling processes compared to the alveoli, suggesting that hypoxia may be a driver of pathogenesis in chronic lung disorders.